Address in Portuguese and Spanish Studies in Diachrony and Diachronic Reconstruction - Hummel, Martin; dos Santos Lopes, Célia (De Gruyter, 2020)
The volume provides the first systematic comparative approach to the history of forms of address in Portuguese and Spanish-two intimately related languages sharing historical, political and geographic contexts. Including theoretical reflections as well as fine-grained empirical studies, the volume relies on an innovative methodology, as it links traditional downstream diachrony with upstream diachronic reconstruction based on synchronic variation.